Fotoiniciadores aplicados em processos de fotopolimerização para impressão 3D - Medeiros, Maiara da Silva (Universidade Federal de São Carlos, 2025)
One of the most relevant additive manufacturing techniques is 3D printing by photopolymerization, enabling the production of complex structures with high precision and tunable mechanical properties. In this context, photoinitiators play a crucial role, since their proper selection directly influences curing rate, dimensional stability, and process safety. This work aimed to conduct a systematic and exploratory literature review on the mechanisms of action of photoinitiators (radical and cationic, including Norrish Type I and II reactions); their selection criteria, such as spectral compatibility, polymerization kinetics, and practical requirements; as well as their applications; limitations; and recent advances. The methodology was based on the critical analysis of scientific articles, theses, and patents published in the last decade, retrieved from national and international academic databases. The results showed that radical systems provide high curing speed but are limited by oxygen inhibition, whereas cationic systems exhibit lower volumetric shrinkage and higher stability, although they are slower and moisture-sensitive. Furthermore, a growing trend was observed towards the development of visible-light-activated photoinitiators and hybrid systems, which combine efficiency and sustainability, with promising applications in biomedical and advanced industrial fields. It is concluded that the evolution of photoinitiators for 3D printing is directly associated with the pursuit of solutions that integrate technical performance, safety, and environmental sustainability, paving the way for future developments in bioprinting and sustainable manufacturing.
Photoinitiators applied in photopolymerization processes for 3D printing
Keywords: Fotopolimerização; Fotoiniciadores; Manufatura aditiva; Photoinitiators; Photopolymerization; Additive manufacturing; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::POLIMEROS E COLOIDES; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::FOTOQUIMICA ORGANICA; 12. Consumo e Produção Responsáveis; 9. Indústria, Inovação e Infraestrutura